Rebellion of the Girls: Traces of Feminist Memory in Argentina - Lenguita, Paula Andrea (2022)
Following the people s outcry of the Not One Less movement in Argentina the question has arisen of how to construct a history of Argentine feminism that contains the antecedents of this manifestation In this sense this paper has adopted a combination of theoretical approaches to the militant heritage of the political movement in the last half century re-establishing the contributions of the Argentine Feminist Union 1970-1976 and the National Encounters of Women 1986-2019 The hypothesis is that in these legacies lie the organisational keys to the women s movement and the antecedents of the so-called Rebellion of the Girls in the Not One Less movement This is a brand new political phenomenon for national feminism which has had international repercussions due to its narrative power through social networks Different testimonies of leading participants have been considered with the aim of contributing to a remembrance of the deliberative and narrative modes of the recent feminist experience in Argentina associated with horizontal participation and heterogeneity in ideological positions providing people support for the political scope of these manifestations.